Extension of Indication for Authorised Oncology Products in the European Union: A Joint Effort of Multiple Stakeholders - Mulder, Jorn; Verjans, Robin; Verbaanderd, Ciska; Pean, Elias; Weemers, Just; Leufkens, Hubert G. M.; Pignatti, Francesco; de Boer, Anthonius; Voest, Emile E.; Stoyanova-Beninska, Violeta V.; Pasmooij, Anna M. G. (Frontiers in Medicine, 2021)
After marketing authorisation, the development of a medicinal product often continues with studies investigating new therapeutic indications. Positive results can potentially lead to changes to the terms of the marketing authorisation, such as an extension of therapeutic indication(s). These studies can be initiated and sponsored by the marketing authorisation holder (MAH) or by others. When results from an investigator-initiated trial suggest that an authorised medicinal product is safe and effective for a new therapeutic indication, physicians may want to treat their patients with this medicinal product. In such a situation, it is desirable to extend the therapeutic indication(s) via the regulatory approval process, as this can facilitate patient access within the European Union. There may however be challenges when the MAH did not conduct the study and might not have access to the data. In this perspective, we focus on the possibilities to extend the therapeutic indication(s) of an already authorised medicinal product based on results from investigator-initiated trials. We address: 1) the advantages of an extension of indication; 2) the regulatory requirements for a variation application; 3) investigator-initiated trials as a basis for regulatory approval; 4) the role of the MAH in extending the indication. With this article, we want to emphasize the importance of a collaborative approach and dialogue between stakeholders with the aim to facilitate access to effective medicinal products.